Non-Prototypical Reduplication - Urdze, Aina (Studia typologica ;, 2018)
As "reduplication" is a continuously discussed topic in the field of linguistic typology and morphology there is still the need to reach a deeper understanding of reduplicative processes. This volume aims to explore the boundaries of reduplication proper from an outside angle, i.e. by looking into non-prototypical cases which challenge the formal and functional criteria for reduplication proper. The articles selected cover various linguistic areals from Southeast Asia, Africa and Europe. Abbi explores echo formations and reduplicative expressives in Southeast Asia. Anderson presents an in-depth study on various reduplication phenomena in the Munda language family. Nintemann addresses a formal problem of reduplication proper in Bantu languages. Finkbeiner discusses a case of triplication in German, contrasting it with the framework of reduplication. Kallergi & Konstantinidou provide an detailed insight into several kinds of echo formations in Modern Greek, including diachronic aspects. Rozhanskiy's focus is on unexpected reduplicative patterns found in the formation of Komi ideophones. Stolz delivers a thorough crosslinguistic investigation on reduplicative phenomena, favouring the canonical approach over the prototype method.